2011 IEEE International Symposium on Parallel and Distributed Processing Workshops and PHD Forum 2011
DOI: 10.1109/ipdps.2011.194
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Monopolies in Colored Tori

Abstract: The {\em information diffusion} has been modeled as the spread of an information within a group through a process of social influence, where the diffusion is driven by the so called {\em influential network}. Such a process, which has been intensively studied under the name of {\em viral marketing}, has the goal to select an initial good set of individuals that will promote a new idea (or message) by spreading the "rumor" within the entire social network through the word-of-mouth.\ud Several studies used the {… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…The debate about social relevant issues spreads and persists over the web by leading to the emergence of unprecedented social phenomena such as the massive recruitment of people around common interests, ideas or political visions 9 10 11 12 . In the past years an intensive research effort has been payed in understanding social phenomena from innovation diffusion, to social influence, up to opinions and their dynamics 13 14 15 16 17 18 19 20 21 22 23 ; some of them have focused on the role of media 24 25 26 27 28 29 30 31 and of the web 32 33 .…”
mentioning
confidence: 99%
“…The debate about social relevant issues spreads and persists over the web by leading to the emergence of unprecedented social phenomena such as the massive recruitment of people around common interests, ideas or political visions 9 10 11 12 . In the past years an intensive research effort has been payed in understanding social phenomena from innovation diffusion, to social influence, up to opinions and their dynamics 13 14 15 16 17 18 19 20 21 22 23 ; some of them have focused on the role of media 24 25 26 27 28 29 30 31 and of the web 32 33 .…”
mentioning
confidence: 99%
“…The WAs effect is relevant when the global tolerance is fixed to 2: the 30% of WAs is sufficient to invert the effect on mass opinions of the 70% of TWs. Furthermore when tolerance is higher (5), the number of WAs needed to inhibit media is smaller (20%). One may expect that tolerance plays a fundamental role in opinions' convergence toward the media or the WAs values.…”
Section: Emerging Resultsmentioning
confidence: 99%
“…This challenge however is in general difficult due to the NP-hardness results (Kempe et al 2003). Different updating rules could also be investigated: for instance, in Brunetti et al (2011) the authors consider a different model, where a node updates its weight with the weight of the majority of its neighbours. Furthermore, in Ugander (2012) it was observed that the number of connected components in an individual's contact neighbourhood (representing separate social contexts for the user) is more influential than the size of the neighbourhood itself.…”
Section: Conclusion and Open Problemsmentioning
confidence: 99%